Influence of feeding differentiation on the age at onset of puberty in Brazilian Bergamasca dairy ewe lambs - Dantas, A. [UNESP]; Siqueira, E. R. [UNESP]; Fernandes, S. [UNESP]; Oba, E. [UNESP]; Castilho, A. M. [UNESP]; Meirelles, P. R.L. [UNESP]; Sartori, M. M.P. [UNESP]; Santos, P. T.R. [UNESP] (FapUNIFESP (SciELO), 2016)
The objective of the study was to evaluate body growth and age at onset of puberty on lambs fed two specific diets for low and high growth rates. A herd of 20 Brazilian Bergamasca lambs was divided in two groups (n= 10) and kept confined throughout the experimental period, two animals of the same treatment/pen. Two phases were established: Phase 1, from 90 days of age until the onset of puberty; and Phase 2, from puberty onset up to 1 year old. For Phase 1, two distinct diets were formulated, being: Treatment A, which was formulated to obtain an average daily gain of approximately 150g; and Treatment B, for an average daily gain of about 250g. In Phase 2, a balanced, equal diet was provided to both groups. Every 14 days, the animals were weighed and given average daily gain, average daily dry matter intake and body condition score. From the 5th month of age on, in each group, a vasectomized male was used to detect estrus, establishing age at puberty onset and estrus interval for each lamb. Blood samples were collected every 28 days to determine plasma growth hormone concentration. Treatment B lambs gained more weight and had higher body condition score (P < 0.05) and there was no difference for age at puberty onset and plasma growth hormone levels (P > 0.05) between treatments. It was found that both treatments showed satisfactory performances. Thus, treatment A may be indicated as a reasonable feeding system to achieve positive responses on confined ewe lambs during growth phase.
Keywords: Growth hormone; Nutrition; Performance; Reproduction; Sheep